2002
DOI: 10.1097/00002030-200203080-00016
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four month efficacy of a maternal short-course zidovudine regimen to prevent mother-to-child transmission of HIV-1 in West Africa

Abstract: A maternal short-course zidovudine regimen reduces MTCT of HIV-1 at age 24 months, despite prolonged breastfeeding. However, efficacy was observed only among women with CD4 cell counts > or =500/ml. New interventions should be considered to prevent MTCT, especially for African women with advanced HIV-1 immunodeficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 18 publications
2
64
1
2
Order By: Relevance
“…These regimens are widely considered to be similar in efficacy in reducing HIV-1 perinatal transmission [20], however they have not been compared directly in a randomized trial. Transmission risk for zidovudine was higher and for nevirapine was lower in our study than in larger previously published trials of each regimen, but most estimates from previous trials were contained in the 95% CI for our estimates [21][22][23][24]. Although our study was small and not primarily designed to evaluate effects on transmission risk, it suggests that nevirapine may be more effective than short-course zidovudine in decreasing mother-to-child transmission in breastfeeding cohorts and certainly confirms the benefit of this simple regimen.…”
Section: Discussioncontrasting
confidence: 48%
“…These regimens are widely considered to be similar in efficacy in reducing HIV-1 perinatal transmission [20], however they have not been compared directly in a randomized trial. Transmission risk for zidovudine was higher and for nevirapine was lower in our study than in larger previously published trials of each regimen, but most estimates from previous trials were contained in the 95% CI for our estimates [21][22][23][24]. Although our study was small and not primarily designed to evaluate effects on transmission risk, it suggests that nevirapine may be more effective than short-course zidovudine in decreasing mother-to-child transmission in breastfeeding cohorts and certainly confirms the benefit of this simple regimen.…”
Section: Discussioncontrasting
confidence: 48%
“…1 Several trials have reported the efficacy of simple, low-cost antiretroviral prophylactic regimens to reduce mother-to-child transmission of HIV in sub-Saharan Africa. [2][3][4] Although prevention of mother-to-child transmission of HIV (PMTCT) interventions using single-dose nevirapine (sdNVP) have been implemented in many urban and rural clinics in Zimbabwe, 5 uptake of these interventions remains low, primarily due to poor antenatal HIV testing rates. 6 Detection of maternal infection early in pregnancy through voluntary counselling and HIV testing (VCT) is critical for PMTCT.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, more than 90% of their infants are protected against HIV-1 during pregnancy. 6 The antiretroviral therapy, zidovudine (ZDV) is metabolized into its active form in the placenta. 7 ZDV inhibits HIV replication within placental cells.…”
Section: Introductionmentioning
confidence: 99%